Diagnostic Accuracy of Contrast-Enhanced Ultrasound Liver Imaging Reporting and Data System (CEUS LI-RADS) for Differentiating Between Hepatocellular Carcinoma and Other Hepatic Malignancies in High-Risk Patients: A Meta-Analysis - Li, Jiawu; Yang, Lulu; Ma, Lin; Lu, Qiang; Luo, Yan (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Objectives The American College of Radiology (ACR) contrast-enhanced ultrasound liver imaging reporting and data system (CEUS LI-RADS), which includes diagnostic criteria for hepatocellular carcinoma (HCC) and other hepatic malignancies (OM), is increasingly used in clinical practice. This study performed a meta-analysis to assess the diagnostic accuracy of CEUS LI-RADS for differentiating between HCC and OM in high-risk patients.Methods PubMed, Embase (Ovid), and Cochrane (CENTRAL) were searched for relevant studies. All studies that reported the percentage of HCC and OM in the LI-RADS categories were included. Random-effects models were used to calculate the pooled sensitivity and specificity, diagnostic odds ratio (DOR), and summary receiver operating characteristic (SROC) curve.Results Eight studies involving 4215 focal liver lesions were included in the final analysis. The pooled sensitivity and specificity of the LR-5 criteria for HCC were 0.71 (95 % CI, 0.69–0.72) and 0.88 (0.85–0.91), respectively, the DOR was 18.36 (7.41–45.52), and the area under the SROC curve (AUC) was 0.8128. The pooled sensitivity and specificity of the LR-M criteria for OMs were 0.85 (0.81–0.88) and 0.86 (0.85–0.87), the DOR was 27.82 (11.83–65.40), respectively, and the SROC AUC was 0.9098.Conclusion The CEUS LI-RADS can effectively distinguish HCC from other hepatic malignancy in high-risk patients based on LR-5 criteria and LR-M criteria. However, further studies are needed for validation due to the limited number of included studies and the potential heterogeneity among the included studies.
Keywords: contrast-enhanced ultrasound (CEUS); liver; liver imaging reporting and data system (LI-RADS); hepatocellular carcinoma (HCC)